IMPLEMENTATION OF TOPSIS METHOD FOR DECISION SUPPORT SYSTEMS OF DIRECT CASH ASSISTANCE RECIPIENTS (BLT) IMPACT OF COVID-19 IMPACTS OF MICRO SMALL MEDIUM ENTERPRISES (UMKM) IN PAITON DISTRICT, PROBOLINGGO DISTRICT - Anis Nadhiroh; Dewi Agustianingsi; Diajeng Syahdania Syahdania; Dian Prasti M (Unusa Press, 2021)
Efforts Government provides social assistance in order to fulfill all the needs of the economy for the people, especially the business of Micro Small Medium Enterprises are exposed to the impact of the virus covid-19 turned out to be still considered not optimal. So many actors business who think that aid social who do not and have not been precisely targeted and The Government also recognizes the problem that, until the time of this Ministry of Social Affairs and the government is still updating the data in order to precisely target. The case is suspected to be due to data collection that is not in accordance with facts and is not real-time in each region. Inputting the data in manually in the District Paiton Probolinggo risk not the right target, the receiver doubles as well as there are elements – elements that utilize state of the. Be because the methods TOPSIS expected to be able to determine the criteria of Enterprises of Micro Small Medium Enterprises are entitled to receive the assistance of social COVID-19. Method of TOPSIS is a method that uses calculations or that provides the kinds of criteria specified which have a weight of up to the value end of the weight will be the decision final. Method of TOPSIS it refers to the benchmark Enterprises Micro Small Medium Enterprises or actors effort that deserves receive the corresponding data is relevant.